2020
DOI: 10.1007/s00405-020-05816-z
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term evaluation of perioperative i.v. corticosteroid treatment efficacy on overall and audiological outcome following CO2 laser stapedotomy: a retrospective study of 84 cases

Abstract: Purpose Our aim was to determine whether perioperatively administered corticosteroid treatment has any beneficial effect on the outcome of stapes surgery, with special regard to the audiological results and early postoperative morbidity. Methods 84 CO 2 laser stapedotomies performed in our institute between 2013 and 2018 were included in our investigation. All cases underwent preoperative and mid-term postoperative pure-tone audiometric evaluation. Vestibular complications were also evaluated. The cases were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
6
2
1
Order By: Relevance
“…Additionally, vestibular complications, hospital days, and inner ear damage were similar between the two groups. 24 On the contrary, in our study, patients receiving topical dexamethasone during the stapedotomy had a significantly shorter hospital stay compared to placebo group. A shorter hospital stay reduces the total cost and might also alleviate hospitalization complications.…”
Section: Discussioncontrasting
confidence: 67%
“…Additionally, vestibular complications, hospital days, and inner ear damage were similar between the two groups. 24 On the contrary, in our study, patients receiving topical dexamethasone during the stapedotomy had a significantly shorter hospital stay compared to placebo group. A shorter hospital stay reduces the total cost and might also alleviate hospitalization complications.…”
Section: Discussioncontrasting
confidence: 67%
“… 16 Our group was the first to describe that the above-mentioned adjuvant treatment contributes to a significantly better ABG closure after primary CO 2 laser stapedotomy compared with the control group. 17 Our assumption is that this contribution is manifested through the prevention of scar tissue formation.…”
Section: Discussionmentioning
confidence: 99%
“…Szekely et al have reported the efficacy of perioperative use of intravenous corticosteroid treatment. The authors concluded that it could be a subject of further investigation in a prospective manner [20]. None of the patients in the current study had such complications.…”
Section: Discussionmentioning
confidence: 57%